The pedagogical training of teachers in stricto sensu programs in accounting sciences - Laffin, Marcos (2018)
Submitted by Núcleo de Pós-Graduação Administração (npgadm@ufba.br) on 2018-08-31T20:41:12Z No. of bitstreams: 1 The Pedagogical Training of Teachers in stricto sensu Programs in Accounting Sciences.pdf: 300093 bytes, checksum: 4747106797197811307b4e9a1b5c5972 (MD5)